Characterization and In Vivo Assay of Allantoin-Enriched Pectin Hydrogel for the Treatment of Skin Wounds - Saucedo Acuña, Rosa Alicia (2023)
This work describes a liquid allantoin-enriched pectin hydrogel with hydrophilic behavior that is supported by the presence of functional groups related to healing efficacy. A topical study shows the effect of the hydrogel application on surgically induced skin wound healing in a rat model. Contact angle measurements confirm hydrophilic behavior (11.37◦), while Fourier-transform infrared spectroscopy indicates the presence of functional groups related to the healing effectiveness (carboxylic acid and amine groups). Allantoin is distributed on the surface and inside the amorphous pectin hydrogel surrounded by a heterogeneous distribution of pores. This promotes wound drying with better interaction between the hydrogel and cells involved in the wound healing process. An experimental study with female Wistar rats indicates that the hydrogel improves wound contraction, reducing around 71.43% of the total healing time and reaching total wound closure in 15 days.